Governing Mobility Beyond the State - Müller, A. author. aut Link
VIII, 233 p.
Keywords: This book explores the structural tensions and conflicts that arise with the abolition of border controls between the EU's member states and how this conflict ridden relationship affects and is affected by the institutional shape of the EU's external borders.